RANCANG BANGUN WEBSITE PENYEDIA LOWONGAN KERJA DISABILITAS KABUPATEN PASURUAN - M. Noval Riswandha; Kusumawati Andarika (STMIK YADIKA BANGIL, 2020)
Abstract : Design the website of the provider of job vacancy disability Pasuruan is an information system created to help people with disabilities in obtaining jobs in Pasuruan. This information system can be a medium that connects people with disabilities with employers so they can easily get the job they want as normal people do. With this website, it is expected that companies in Pasuruan that have not provided job opportunities for PwDs can participate by registering as a provider of work. So they are recorded in the Manpower Office of Pasuruan Regency as a company that has fulfilled the government regulation as stated in Law No.4 of 1997.